P-Body Components, microRNA Regulation, and Synaptic Plasticity. (2007) - Hillebrand, Jens; Barbee, Scott A.; Ramaswami, Mani
Abstract : What is the protein apparatus required for microRNA (miRNA) function and translational repression in neurons? This article reviews our recent work on Me31B, a conserved P-body protein present on Staufen-containing neuronal and maternal ribonucleoprotein (RNP) particles, which is required for dendrite morphogenesis and miRNA function in vivo . In addition, it provides new data to show that Me31B is present on and regulates formation of P-bodies in the Drosophila wing disc, where it has a general role in the regulation of miRNA function. While illuminating the function of this important RNA regulatory molecule, it also brings into focus a hypothesis of potentially broad significance. Namely, that P-body proteins may play important roles in regulation of dendrite-localized mRNAs and, thereby, in synaptic plasticity. A wide range of protein localization and early functional data support this hypothesis. We also discuss current knowledge of RNP particles that mediate translational repression and the implications of these findings for understanding translational control in neurons.